PENGARUH CITRA MEREK, PROMOSI, DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN TISU BASAH DI KOTA BATAM - lim, safira; Suhardi, Suhardi (LPPM Universitas Putera Batam, 2026)
Growing public awareness of cleanliness and personal hygiene has contributed to the rising demand for wet tissue products in Indonesia. At the same time, intense competition in the market offers consumers many choices when deciding which products to purchase. Therefore, this study aims to examine the effects of brand image, promotional activities, and product quality on consumers’ purchasing decisions regarding Paseo wet tissues in Batam City. This research applies a quantitative approach using a survey method, with 120 respondents who have purchased or used Paseo wet tissues in Batam City. The data were analyzed using multiple linear regression with SPSS software. The findings show that brand image, promotion, and product quality each have a significant partial effect on purchasing decisions. In addition, these variables simultaneously have a significant influence on purchasing decisions. The results of this study are expected to serve as a reference for companies in formulating effective marketing strategies to improve product competitiveness.